Оn the genesis and essence of the process of digitalization of global economic development - Alina Shevtsova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
The development of digital technologies in the context of economic globalization has led to significant changes that have determined the gradual transition from an industrial to a digital economy. This transition is reflected in the digitalization of business processes, the introduction of digital technologies in the activities of industrial enterprises, service organizations, government agencies, and financial institutions. The subject of the article is the process of digitalization of global economic development. The aim is to study the genesis and determinants of the development of the digitalization process by analyzing the publication activity on the conceptualization of the concepts of “digitization”, “digitalization”, “digital transformation”. Methods: the historical method and comparative analysis were used to study the genesis and determinants of the development of the digitalization process; statistical analysis was used to analyze the publication activity on the conceptualization of the concepts of “digitization”, “digitalization”, “digital transformation”; the logical method was used to determine the essence of the process of digitalization of global economic development. The following results are obtained: based on the analysis, it is noted that the genesis of the process of digitalization of global economic development can be considered in several stages: 1) the pre-digital stage; 2) the initial stage of digitization; 3) the stage of digitization of processes; 4) the stage of development of network technologies; 5) the stage of e-commerce and business Internet; 6) the stage of artificial intelligence and data analysis; 7) the stage of the digital transformation boom. Based on the clarification of the essence of the concepts of "“digitization”, “digitalization”, “digital transformation” it was argued that digitization lays the foundation for digitalization, and digitalization provides the possibility of digital transformation. Conclusions: in today's world, digital transformation has become a key aspect that determines the competitiveness of countries and enterprises in international markets. Digital technologies determine the direction of the global economy, acting as a catalyst and tool for dynamic transformation in the economic landscape.